Apricot shell- and apple tree-derived biochar affect the fractionation and bioavailability of Zn and Cd as well as the microbial activity in smelter contaminated soil. (September 2020) - Ali, Amjad; Shaheen, Sabry M.; Guo, Di; Li, Yiman; Xiao, Ran; Wahid, Fazli; Azeem, Muhammad; Sohail, Kamran; Zhang, Tao; Rinklebe, Jörg; Li, Ronghua; Zhang, Zengqiang
Abstract: The aim of this study was to elucidate the effects of apricot shell-derived biochar (ASB) and apple tree-derived biochar (ATB) on soil properties, plant growth, microbial communities, enzymatic activities, and Zn and Cd fractionation and phytoavailability in mining soils. Smelter soil contaminated by Zn (1860.0 mg kg −1 ) and Cd (39.9 mg kg −1 ) was collected from Fengxian, China, treated with different doses (0 (control), 1, 2.5, 5, and 10% w/w) of both biochars and cultivated by Brassica juncea in a greenhouse pot experiment. The acid-soluble, reducible, oxidizable, and residual fraction and plant tissue concentrations of Zn and Cd were determined. Biochar addition improved plant growth (22.6–29.4%), soil pH (up to 0.94 units), and soil organic matter (up to 4-fold) compared to the control. The ASB and ATB, particularly ATB, reduced the acid-soluble (21–26% for Zn and 15–35% for Cd) and the reducible (9–36% for Zn and 11–19% for Cd) fractions of Zn and Cd and altered these fractions in the organic and residual fractions. Therefore, the biochars decreased the metal concentrations in the roots (36–41% for Zn and 33–37% for Cd) and shoots (25–31% for Zn and 20–29% for Cd), which might be due to the increase in pH, biochar liming effects, and metal sorption by the biochar. The biochars impact on the bacterial community composition was selective. The ASB and ATB decreased the activities of soil β-glucosidase, dehydrogenase, and alkaline phosphatase while increasing the urease activity. The biochars, particularly ATB, can be considered as effective soil amendments for reducing the phytotoxicity of Zn and Cd in contaminated soils, improving plant growth, enhancing the abundance of specific bacterial groups and increasing urease activity; however, more attention should be paid to their negative effects on the activities of β-glucosidase, dehydrogenase, and alkaline phosphatase. Graphical abstract: Image 1 Highlights: Apricot shell- (ASB) and apple tree-biochar (ATB) immobilized soil Zn and Cd. ASB and ATB reduced acid soluble and reducible Zn (26–36%) and Cd (19–35%). ASB and ATB altered soluble and reducible Zn and Cd to organic and residual fraction. ASB and ATB decreased Zn (31–41%) and Cd (29–37%) in plant tissues. Both biochars improved bacterial community, but decreased enzymes activity.